Chemical composition, antibacterial and toxicity activities of Aquilaria leaves from three commonly planted species in Malaysia - Adam, Aimi Zafirah (2017)
The Aquilaria genus (Thymelaeaceae), is an eminent agarwood-producing tree, commonly found in the Indomalesia region. Illegal harvesting and random logging had caused Aquilaria trees to be listed in the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). In recent years, Aquilaria tree cultivation at large scale has been implemented to promote sustainable agarwood production. Besides utilizing agarwood induced in the tree trunk, the leaves can be processed into food products such as tea, which can give some economic return while farmers wait for their agarwood to mature. In this study, three Aquilaria species, Aquilaria crassna, Aquilaria malaccensis and Aquilaria sinensis were selected because they are widely planted in Peninsular Malaysia. The aim of this study was to validate the leaf specimen of the three Aquilaria species based on morphology and molecular identification, to identify the chemical compounds of the leaves using Gas Chromatography-Flamed Ionization Detector (GC-FID) and Gas Chromatography-Mass Spectrometry (GC-MS) as well as to evaluate the antibacterial and toxicity activity of the leaves. A total of 58 compounds were obtained from the essential oils, and nine and 48 compounds from the hexane and methanol extracts, respectively. Among the major compounds identified were hexadecanoic acid and squalene, which are known to have antimicrobes and antioxidants properties, respectively. Methanol extracts of A. malaccensis exhibited maximum inhibition zones against Staphylococcus aureus and Salmonella choleraesuis. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts (31.25 mg/ml) produced remarkable inhibitory effect on S. aureus compared to S. choleraesuis (250 mg/ml). The MTT test proved that both the essential oils and hexane extracts of the three leaves had no significant effects on the viability of the PBMCs. However, only the methanol extract of A. malaccensis had low levels of IC50 (24.5 mg/ml) and LD50 (4537 mg/kg) values, suggesting this species is slightly hazardous. For the comet test, the three Aquilaria species also did not show any DNA damages (p>0.05). Similar results were obtained when using the methanol extracts of A. crassna and A. sinensis at 2 mg/ml and 3 mg/ml, respectively. However, for the methanol extracts of A. malaccensis leaves, DNA damage was observed (p<0.05). The tests conducted on PBMCs indicated that the essential oils and crude extracts of Aquilaria leaves from these three species are relatively safe to consume without major toxicity concern, but should be wisely taken in a dose-dependent manner. This study provides a benchmark in setting up indicators for measuring toxicity threats from the use of Aquilaria leaves, which is becoming a popular ingredient in food or drinks preparation.